Determination of Mercury Impurities in Protamine Sulfate Medicament by Stripping Voltammetry - N. O. Kim; E. A. Ivanovskaja (Разработка и регистрация лекарственных средств, 2019)
Introduction. The article presents data of the quantitative mercury determination in an aqueous solution of the pharmaceutical substance protamine sulfate by stripping voltammetry on graphite electrodes modified with a gold-polymer composition. The existing method to determine the mercury impurity in protamine sulfate according to the European Pharmacopoeia – multistage titration with dithizone – is laborious and does not allow to achieve repeatability.Aim. Analyzing the content of bioaccumulative mercury impurities in a protamine sulfate solution by stripping voltammetry. Materials and methods. Protamine Sulfate Substance (Manufacturer Alps Pharmaceutical Industry Co.Ltd). Experimental data were obtained on a TA-4 semi-automatic analyzer (LLC NPP Tomianalit, Tomsk) with VALabTx software.Results and discussion. We adapted the method for mercury determination in water and presented the results of its testing on protamine sulfate solution. The results of testing the electrode operation using the «entered-found» method are given, the results of a single mercury analysis were included in the interval 0, 0038–0,0063 mg/l, which confirms their readiness for work. This interval is registered in the methodology and means the limits of permissible deviations. The limits of detection of mercury on the device are 10-6 –10-10 mol/l. We prepared a solution with concentrations of 10 mg/m from the protamine sulfate substance and measured it on prepared electrodes. The mercury content in the test sample was 0.00034 mg/l. According to the certificate of protamine sulfate, the mercury content should be ≤10 ppm. We studied the effect in changing of accumulation time. The optimal accumulation time was 80 seconds, because under standard conditions, not all mercury concentrates on the electrode surface, and above 80 seconds there is no significant increase in mercury content.Conclusion. The proposed method for mercury determination in water by stripping voltammetry on graphite electrodes modified with a gold-polymer composition can be adapted to determine bioaccumulative mercury in the pharmaceutical substance protamine sulfate. The findings suggest that this method can be used in quality control of medicines, as an alternative express method for mercury impurities determination to the existing multistage titration method with dithizone.